FACTORS INFLUENCING BENEFICIARIES ACCESS TO FADAMA NG-CARES PROGRAMME IN WESTERN ZONE OF BAUCHI STATE, NIGERIA - John, V.; Garba, M.; Usman, A. B. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study examined the effects of the Fadama NG-CARES programme on the livelihoods of beneficiaries in the Western Agricultural Zone of Bauchi State, Nigeria. A multistage sampling procedure was used to select 270 respondents from the study area. Data were collected through the administration of structured questionnaires and analyzed using descriptive statistics and logit regression. The findings revealed that majority (60%) of the respondents were male and 91.5% were married, with majority (81.5%) attended secondary or tertiary education. Farming constituted the primary occupation (99.3%) of the respondents. The leading sources of information on the programme were fellow farmers (59.6%), radio (56.3%), community leaders (55.2%), and Fadama desk officers (54.8%). The result further showed that age and land acquisition method negatively and significantly (P<0.05) influenced respondents’ access to the fadama NG-care programme, while secondary occupation and market access positively and significantly (P<0.05) influenced respondents’ access to the programme. The study concluded that age, secondary occupation, access to markets and land acquisition were the factors influencing beneficiaries’ access to NG-cares programme. It is recommended that policy makers strengthen land tenure security, promote youth engagement, expand market linkages, and improve gender inclusion to maximize the impact and sustainability of the Fadama NG-CARES programme.